GENOTOXIC IMPURITIES: AN IMPORTANT REGULATORY ASPECT - R POUNIKAR, ANITA; J UMEKAR, MILIND; R GUPTA, KRISHNA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Genotoxins are agents/carriers such as chemical or radiation that can cause the damage to DNA or chromosomal structure, thereby causing mutations and the process are called as genotoxicity. Identification and understanding of genotoxins at a primary stage of drug development would enable us to prevent the potential damage that can be caused by these genotoxic agents. Various regulatory agencies such as International Council for Harmonization and EMEA, USFDA, European Pharmacopeia guidance, guidance for oncology products provide guidelines to limits the level of impurities in drug substances and drug products. Nowadays, conventional protocol of isolation, various spectral analysis high-performance liquid chromatography (LC), Fourier transform infrared to on-line analysis using modern, sophisticated hyphenated tools, like gas chromatography-mass spectroscopy, LC-MS so on, as well as modern software based in silico drug designs are extensively used by industry, research, and development areas and also there is tremendous increase in publications in the literature involving their use. Our review article focused on the various regulatory guidelines, application of hyphenated tools, and in silico techniques in genotoxic impurity and degradation product profiling of small molecules. A brief explanation is made on possible pitfalls in the experimentation and data interpretation. From this review, it concluded that there are various countries having their own regulatory agencies and regulatory guidelines for drug approvals, which may be followed by applying new chemical entities the new drug application title (NDA) in new drug application as well as there are various conventional to modern software based techniques to quantification of genotoxic impurities.